Funding and Taxation of Greek Non Profit Organizations and Enterprises - Chrysanthi Balomenou; Michael Bekiaris; Maria Lagou (European Regional Science Association (ERSA), 2006)
Surely, the economic aspect of non profit organizations is very interesting. The aim of the enterprises of this type is not to maximize their profits but to minimize their operational expenses, in order to survive. Therefore, the objective of non profit organizations is to ensure any possible financial resources and to exempt taxes. It is agreed that financial seeking and tax exemption are of crucial importance for the vitality of non profit organizations and companies. This paper studies the following issues: i. The modern approach regarding non profit sector and its social role. Ii. Funding resources and ways to support the non profit organizations and enterprises. iii. Law restrictions regarding the taxation of the non profit organizations and enterprises. iv. Financial operation and management of the non profit organizations and enterprises. v. Evaluation of the financial and taxation framework related with non profit organizations and enterprises operational processes. vi. Conclusion- suggestions for future policy actions.
Keywords: 330